Assessing the kinetics of microbubble appearance in cirrhotic patients using transthoracic saline contrast‐enhanced echocardiography. Issue 10 (25th August 2017) - Tonelli, Adriano R.; Naal, Tawfeq; Dakkak, Wael; Park, Margaret M.; Dweik, Raed A.; Stoller, James K.
Abstract : Background: The number of cardiac cycles that need to be reviewed by echocardiography before a significant intrapulmonary shunt can be excluded remains unclear. Methods: We retrospectively identified patients with cirrhosis who underwent technetium‐99 m‐labeled macroaggregated albumin scanning. The kinetics of bubble appearance after the injection of agitated saline during transthoracic echocardiograms were assessed in these patients. Results: For the 64 eligible patients, the mean ± SD age was 56 ± 9 years. The median (IQR) shunt fraction by radionuclide scanning was 7.7% (2.8%–19.9%). Microbubbles were seen in the left atrium (LA) and left ventricle (LV) at a median (IQR) of 4 (2–5) and 4 (2–5) beats, respectively. The number of heart cycles before microbubbles appeared in the LA or LV was inversely associated with the nuclear scanning shunt fraction ( R  = −0.42, P  = .001, R  = −0.46, P  < .001, respectively). If no microbubbles were detected by heart cycle 7, the shunt fraction was uniformly less than 3%. Patients with arterial oxygen <60 mm Hg, compared to ≥60 mm Hg, had earlier appearance of microbubbles in the left heart chambers (2.6 ± 1.9 vs 4.0 ± 2.3 beats, P  = .046). Conclusions: In patients with advanced cirrhosis suspected of having hepatopulmonary syndrome, a greater shunt fraction during nuclear scanning was associated with more pronounced hypoxemia and a prompt and more intense appearance of microbubbles in the left‐sided heart chambers. Patients with a shunt fraction above 3% have microbubbles in the LA or LV at some point during the first seven heart cycles.